Lancelets (Cephalochordata: Branchiostomatidae): How many species are valid? - Poss, S. G.; Boschung, H. T. (Isr. J. Zool, 1996)
Fifty specific and ten generic names have been applied to lancelets living in tropical and subtropical oceans. About 29 of the names represent valid taxa, distinguishable on the basis of meristic variation and assignable to the genera Branchiostoma and Epigonichthys. Branchiostoma has gonads on both sides of the body and its bilateral metapleural folds terminate immediately posterior to the atriopore. Epigonichthys normally has gonads present on the right side only and the metapleural fold of the left side is confluent with the anterior terminus of the caudal fin. Traditionally, myomere counts, counts of fin chambers, position of atriopore and anus, and qualitative differences in notochord and caudal fin shape have been used to distinguish species. Multivariate analysis of meristic variation, using primarily American species, reveals considerable intraspecific variability in key taxonomic features. Some species exhibit wide variation in countable segments, whereas others are characterized by a narrow range. This report includes primary synonymies, diagnoses, distributions, and nomenclatural remarks for all taxa recognized.